Structural characterization of an etheno-2 '-deoxyguanosine adduct modified by tetrahydrofuran - Loureiro, APM; Campos, IPD; Gomes, O. F.; Possari, EPM; Di Mascio, P.; Medeiros, MHG (Amer Chemical Soc, 2005)
The reaction of 2'-deoxyguanosine with the alpha,beta-unsaturated aldehydes trans-2-octenal, trans-2-nonenal, trans-2-decenal, trans,trans-2,4-nonadienal, and trans,trans-2,4-decadienal in THF gives rise to three novel adducts: 3-(2'-deoxy-beta-D-erythro-pentafuranosyl)-7-[3-hydroxy-1-(3(2'-deoxy-beta-D-erythro-pentafuranosyl)-3,5-dihydro-imidazo[1,2-alpha]purin-9-one-7-yl)-propyl] -3,5-dihydro-imidazo[1,2-alpha]purin-9-one (M) and 3-(2'-deoxy-beta-D-erythro-pentafuranosyl)-7-(tetrahydrofuran-2-yl)-3,5-dihydro-imidazo[1,2-alpha]purin-9-one (A8 and A9), which are not observed in the absence of THF. These adducts were isolated from in vitro reactions by reversed-phase HPLC and fully characterized on the basis of spectroscopic measurements. Adduct A7 consists of two 1,N-2-etheno-2'-deoxyguanosine (1,N-2-epsilondGuo) residues linked to a hydroxy-carbon side chain; adducts A8 and A9 are interconvertible 1,N-2-epsilondGuo derivatives bearing a THF moiety. The proposed reaction mechanism involves the electrophilic attack on 1,N-2-epsilondGuo by the carbonyl of 4-hydroxy-butanal, generated via ring opening of alpha-hydroxy-THF (THF-OH), yielding adducts A8 and A9. A further combination of these adducts with another 1,N-2-epsilondGuo produces the double adduct A7. These findings demonstrate that reactions of unsaturated aldehydes in the presence of THF produce novel condensation 1,N-2-epsilondGuo-THF adducts. Further studies would indicate the relevance of these adducts in THF toxicity.